Implementasi Finite State Machine pada Sistem Notifikasi Pesanan Food Court - Dionisius Marcello Divito; Agung Setia Budi; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Food Court is one of the people's favorite places to find food, drinks, and snacks. But the problem of long lines waiting for orders can lead to problems such as the transmission of the COVID-19 disease and the possibility of a decrease in the number of customers due to not waiting in line. This queuing problem has been overcome by the existing system, the Restaurant Ordering Paging System, but this system has a weakness, namely there is no clarity on the order status. The purpose of this research is to build a new system and tool that has a 1602 LCD feature to display messages from the order status, and also features changing the message content according to user needs. In this system, the Finite State Machine will be used as a method of how the system works to achieve system goals, so that to perform its function, each node in the system needs to move between states according to the state of its objective function. The system obtained from this research is divided into 2 tools, namely the restaurant node and the customer node, with the restaurant node having 4 states, namely the default state, programming mode state, reading user input state, and data sending state. On the other hand, the restaurant node also works with 4 states, namely the default state, LCD blinking state, LCD blinking state with beep buzzer, and state delay for 1 minute. The results obtained from this study are the success of data transmission by 90% from the 4 state tests used, with 2 customer nodes, 1 restaurant node, and the test was repeated 16 times.